Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko
Wydawnictwo:Nowa Era
Rok wydania:2014
Oblicz 4.34 gwiazdek na podstawie 6 opinii

`a)\ root(5)(-3,2)*root(5)(-0,0032)=root(5)(-3,2*(-0,0032))=root(5)(3,2*0,0032)=root(5)(32*0,1*0,0001*32)=` 

`\ \ \ =root(5)(32*0,00001*32)=root(5)32*root(5)(0,00001)*root(5)32=2*0,1*2=0,4` 

`b)\ root(3)(-0,064)*root(3)(0,008)=-0,4*0,2=-0,08` 

`c)\ root(3)(-0,04)*root(3)(-0,36)*root(3)(-0,12)=root(3)(-0,04*(-0,36)*(-0,12))=root(3)(-0,04*0,36*0,12)=` 

`\ \ \ =root(3)(-4*0,01*4*9*0,01*4*3*0,01)=root(3)(-64*27*0,000001)=` 

`\ \ \ =root(3)(-64)*root(3)27*root(3)(0,000001)=-4*3*0,01=-0,12` 

`d)\ root(3)(-3 3/4):root(3)(-1 23/25)=root(3)(-15/4):root(3)(-48/25)=root(3)(-15/4:(-48/25))=root(3)(15/4:48/25)=` 

`\ \ \ =root(3)(strike15^5/4*25/strike48^16)=root(3)(125/64)=5/4=1 1/4` 

`e)\ root(5)(15/64):root(5)(-7,5)=root(5)(15/64:(-7,5))=root(5)(15/64:(-7 1/2))=root(5)(15/64:(-15/2))=root(5)(strike15^1/strike64^32*(-strike2^1/strike15^1))=root(5)(-1/32)=-1/2` 

`f)\ root(3)(root(5)((-32)^3))=root(3)(root(5)(((-2)^5)^3))=root(3)(root(5)(((-2)^3)^5))=root(3)((-2)^3)=-2`